Use of Modified Atmosphere Packaging to Preserve Mushroom Quality during Storage - Palacios, Irene; Moro, Carlos; Lozano, Miguel; D'Arrigo, Matilde; Guillamon, Eva; Garcia-Lafuente, Ana; Villares, Ana (Recent Patents on Food, Nutrition & Agriculture, 2011)
Mushrooms have attracted much attention due to their excellent nutritional and sensory properties. However, they are highly perishable and rapidly lose their organoleptic characteristics. Many methods have been employed for mushroom storage, such as packaging, blanching, canning, or freeze drying. Among them, modified atmosphere packaging (MAP) has been widely employed for preserving fresh mushrooms. MAP provides an affordable packaging system that partly avoids enzymatic browning, fermentation and other biochemical processes by maintaining a controlled gas atmosphere. Several factors, including optimum CO2 and O2 partial pressures, permeability, package material, thickness, or product weight, must be considered in order to design a suitable modified atmosphere package for mushrooms. Thus, different strategies are available to preserve mushroom quality after harvest. The article presents some promising patents on use of modified atmosphere packaging to preserve mushroom quality during storage.
Keywords: Gas Permeability